Is Balint training associated with the reduced burnout among primary health care doctors?. Issue 1 (1st January 2018) - Stojanovic-Tasic, Mirjana; Latas, Milan; Milosevic, Nenad; Aritonovic Pribakovic, Jelena; Ljusic, Dragana; Sapic, Rosa; Vucurevic, Mara; Trajkovic, Goran; Grgurevic, Anita
ABSTRACT: The aim of our study was to examine whether the participation in Balint group is associated with the reducing burnout syndrome among primary health care doctors. This investigation was conducted on a population of 210 doctors employed in primary health centers in Belgrade. Out of 210 doctors, 70 have completed Balint training for a period of at least 1 year, whereas 140 doctors have never attended this training (the Non-Balint group). The level of burnout among physicians was assessed with the Serbian translation of the original 22-item version of the Maslach Burnout Inventory – Human Services Survey which defines burnout in relation to emotional exhaustion, depersonalization and personal accomplishment. We found that 45.0% of the Non-Balint participants and 7.1% of the Balint-trained participants responded with symptoms of high level of emotional exhaustion, with a statistically significant difference ( p < 0.001). In relation to depersonalization, 20% of the Non-Balint subjects were highly depersonalized compared to 4.4% of the Balint-trained subjects, with a statistically significant difference ( p < 0.001). Regarding the personal accomplishment, 21.4% of the Non-Balint subjects and 7.1% of the Balint-trained subjects had a perception of low personal accomplishment, with a statistical significance ( p < 0.001). In the multiple ordinal logistic model, with emotional exhaustion as a dependent variable, statistically significant predictor was female gender (OR = 2.51; p = 0.021), while Balint training was obtained as a protective factor (OR = 0.12; p < 0.001). Non-specialists were detected as a risk factor for depersonalization (OR = 2.14; p = 0.026) while Balint group was found as a protective factor (OR = 0.10; p < 0.001), according to the multiple ordinal logistic regression analysis. Regarding the reduced personal accomplishment, our results indicated that nonspecialists were at risk for this subdimension (OR = 2.09; p = 0.025), whereas Balint participants were protected (OR = 0.18; p < 0.001). Participation in Balint groups is associated with the reduced burnout syndrome among primary health care doctors